THE EFFECT OF LAYER THICKNESS AND RASTER ANGLES ON TENSILE STRENGTH AND FLEXURAL STRENGTH FOR FUSED DEPOSITION MODELING (FDM) PARTS - Abdullah, Z.; Ting, H.Y.; Ali, M.A.M.; Fauadi, M.H.F.M.; Kasim, M.S.; Hambali, A.; Ghazaly, M. M.; Handoko, F. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Additive manufacturing(AM) technologies using Fused Deposition Modeling (FDM) is one of the most popular method and is widely used for prototyping and production application. However, the quality of parts produced with FDM can be affected by various process parameters used. Therefore, this study aims to examine the effect of and layer thickness and raster angle on mechanical properties of FDM parts. All the test specimens were built by using Folger Tech 3D printer with two materials which are ABS and PLA. ASTM D638 and D790 standard were followed to carry out the tensile test and flexural test to determine the mechanical properties of tensile strength, and flexural strength. The influence of the layer thickness and raster angle on tensile strength and flexural strength is determine using Analysis of variance (ANOVA). The results show that the variables layer thickness and raster angle affect the flexural strength more than these variables affect the tensile strength of the test specimen. Contrary to the common results, the specimen fabricated using PLA material has higher strength compared to ABS material in this study.